IFC 2004 Annual Report : Adding Value to Private Sector Investment, Volume 1 - International Finance Corporation (Washington, DC, 2013)
For the fiscal year ended June 30, 2004, the International Finance Corporation (IFC) expanded its sustainable development impact through private sector project financing operations and advisory activities. This year the Board of Directors approved a number of investments and maintained close oversight of development and implementation of IFC strategy. The Board was heavily involved in discussion of IFC's strategic directions, which outline the overall framework for future IFC activities. The Board urged IFC to collaborate more closely with other World Bank Group institutions, especially in providing technical assistance on the business climate and private sector development. In this regard, Directors were pleased to note the increased cooperation between IFC and IDA in Africa. The Board also reviewed country-specific operations and discussed 15 joint World Bank-IFC-MIGA country assistance strategies and related products. Directors noted the challenges in both maintaining profitability and increasing development impact, and they reaffirmed their support of IFC's focus on frontier markets, with a particular emphasis on small and medium enterprises; innovative financing mechanisms; "south-to-south" investments; long-term partnerships; infrastructure; and health and education. Specific issues Directors discussed with IFC management include the update of the IFC's Safeguard Policies and associated guidelines, the review of IFC's Policy on Disclosure of Information, an assessment of IFC's strategy and procedures for donor funded operations, and, in conjunction with other units of the World Bank Group, the Extractive Industries Review. These discussions were ongoing into FY05, along with a proposal to establish a technical assistance and advisory fund to provide sustainable financial support for the Corporation's growing technical assistance activities.